(3GdESJKeGQ aj GdEbJUGO GdSjGSj hGdESdGej hJTQjYGJ hGJaGbjGJ GdESJKeGQs - (3eMeO(B, (3ZGfes ((3GdEScfOQjI(B:s (3OGQ GdacQ GdLGeYj(B,s, 2011)
(3eaghe GdESJKeGQ hGdeSJKeQ aj Yde GdEbJUGO hGdbGfhf(B- (3eaghe GdESJKeGQ hGdeSJKeQ aj bhGfjf GdESJKeGQ GdeUQjI hbhGfjf GdESJKeGQ aj GdOhd GdYQHjI hGdEJaGbjGJ GdEbdjejI(B- (3eaghe GdESJKeGQGJ hGdeSJKeQ aj GdEJaGbjGJ GdOhdjI(B((3GdLeGYjI(B- (3GdEbdjejI(B- (3GdKfGFjI(B) - (3eGgjI GdESJKeGQ aj GdfXGe GdEbJUGOj GdCSdGej heOi eTQhYjJgs
Keywords: (3GdESJKeGQs; (3GdEbJUGO GdGSdGejs; (3GdEbJUGO GdSjGSjs